Pembelajaran Pendidikan Agama Islam Berbasis Wawasan Multikultural Guru untuk Membudayakan Demokrasi dan Toleransi Siswa - Septiyana (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
The conditions and phenomena of Indonesian society, which are very pluralistic in terms of ethnicity, race, religion and social status, have made an extraordinary contribution to the development of dynamics in society. This study aims to analyze the implementation of Islamic Religious Education (PAI) learning, teachers' multicultural insights in PAI learning, and their role in cultivating democracy and tolerance among students at SMK Negeri 1 and SMA Negeri 2 in Cimahi City. Using a qualitative method with a descriptive-analytic approach, this study intends to obtain empirical and objective descriptions. Data collection was conducted through observation, interviews, and documentation. The results show that the implementation of Islamic Religious Education (PAI) learning in both schools has been optimal and aligns with the objectives, methods, materials, tools/media, and evaluations. Teachers' multicultural insights, which encompass thought patterns, attitudes, and behaviors, can be applied in PAI learning. The role of PAI teachers' multicultural insights, which include understanding the reality of diversity, managing learning skills (pedagogy), and forming cultured students (enculturation), is essential for cultivating democracy and tolerance among students.